High quality housing estate planning for greater Yangon metropolitan region - Wann Maung , Zar Zar (2008)
Improvement in space requirements and building services becomes more and more sophisticated because of the technological changes and changes of living style. Moreover, changes in life style of the citizens, family size and structure mainly effect the consideration of today’s Architectural Planning. Housing estate development is therefore more essential and reasonable to create quality living standard and pleasant environment. Many countries accept that housing estates can be able to provide not only better security, more pleasant and healthful environment and quality living standard but also quality of life issues. Housing estates have been remarkably redeveloped in Yangon City after 1993 and it has been improving in the architectural design of the estates and amenities of the community. Most estates can provide some amenities and some estates have been built without considering to neighborhood condition. It is, therefore, required to carry out a detailed analysis in housing estate planning. Physical planning of the site is analyzed by layout plan and site densities. Communities facilities provided are found by analysis on the existing situation of residence inhabitants, family size and structure of housing estates. Finally, high quality housing estate is defined by correlation between physical planning and communities’ facilities. The existing situation of residence inhabitants are known by questionnaires survey on residents. The main focus of this research has been to analyze the existing housing estates condition in Yangon and to recommend the factors for future housing estates planning to meet the users’ requirements and to relevant their environment.